Prospective Memory and Positivity Bias in the COVID-19 Health Crisis: The Effects of Aging - Aizpurua, Alaitz; Migueles, Malen; Aranberri, Ainara (Frontiers in Psychology, 2021)
This study aimed to determine whether the observed tendency to remember more positive than negative past events (positivity phenomena) also appears when recalling hypothetical events about the future. In this study, young, middle-aged, and older adults were presented with 28 statements about the future associated with the Covid-19 pandemic, half positive and half negative. In addition, half of these statements were endowed with personal implications while the other half had a more social connotations. Participants rated their agreement/disagreement with each statement and, after a distraction task, they recalled as many statements as possible. There was no difference in the agreement ratings between the three age groups, but the participants agreed with positive statements more than with negative ones and they identified more with statements of social content than of personal content. The younger and older individuals recalled more statements than the middle-aged people. More importantly, older participants recalled more positive than negative statements (positivity effect), and showed a greater tendency to turn negative statements into more positive or neutral ones (positivity bias). These findings showed that the positivity effect occurs in even such complex and situations as the present pandemic, especially in older adults. The results are discussed by reference to the notion of comision errors and false memories resulting from the activation of cognitive biases